(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Knowledge management in health care is a hot cake to study. Since this sector is heavily relying on the knowledge of different ingredients, and evidence based medicine is expected to be implemented in daily health care activities; besides, delivery of care replies on cooperation of several partners that need to exchange their knowledge in order to provide quality of care. IN health care a knowledge based treatment and consultancy is most required things in contemporary scenario. Since lot more challenges are lies in the way of knowledge management. In public health decision is mainly based on data and a shift is needed towards evidence based decision making. It is obvious that health care can profit from many advantages that KM can provide. Nevertheless, several challenges are ahead, some are proper to KM and other particular to the health care field. This chapter will overview KM, its methods and techniques, and provide and insight into health care current challenges and needs, discuss applications of KM in health care and provide some future perspectives for KM in health care.